Prototipo de nodo sensor multi-propósito para cultivos tropicales - Palma Espinoza, Victor Abelardo (2020)
The need to increase agricultural production with the use of fewer resources has become a priority condition, so that it is possible to obtain specific environmental data to make decisions in the control of production. The purpose of this titling work was the development of the multi-purpose sensing node prototype, with a focus on tropical crops, to be applied within CIIDEA (Ciudad de la Investigación, Innovación y Desarrollo Agropecuario) of ESPAM MFL (Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López). For the development of the prototype the EDER methodology (Estudio, Diseño, Ejecución y Revisión) was used. In its first stage, accurate information about the organization was collected, and the requirements of the institution were determined and analyzed. In the next stage the logical design was created and the node was assembled based on the design. Prototype tests were performed in the laboratories of the University and in the field selected in CIIDEA. Finally, in the review stage the correct functioning of the prototype in the field was demonstrated.